Sei sulla pagina 1di 4

Carnot Engine :Carnot Cycle →Ideal Gas

P

1
Isotherm,T1
2
Adiabatic
4

Isotherm,T2

3

Adiabatic

V

1=>2; ΔU=Q1+W1;

2=>3;q=0,ΔU=W1';

3=>4;ΔU=q2+W2;

4=>1;q=0;ΔU=W2';

Total Work (W)

W=-(w1+w1'+w2+w2')

Heat Input (Q)

Q=q1;

Efficiency (η) η= W/Q=-(w1+w1'+w2+w2')/q1 1 st law

dU = 0 ΔU cycle = 0 = Q + W

That means q1+q2 = -(w1+w1'+w2+w2')

η = ( q 1 + q 2 )

q

1

= 1 + ( q 2 ) <1

q 1

1→2(Isothermal)) Δ U=0; q1 = -W1

2 2

W 1 = q 1 = pdV = RT 1

1

1

dV

V

= RT 1 ln (

V

2

V

3

)

2→3(Adiabatic))

ΔU = C v ( T 2 T 1 )= W' 1

This path is a reversible adiabatic path, Hence:

T

2

T

1

=

(

V

2

V

3

(ϒ 1 )

)

3→4)(Isothermal)ΔU=0; q2= -W2

4

4

W 2 = q 2 = pdV = RT 2

3

3

4→1)(Adiabatic)

ΔU = C v ( T 2 T 1 ) = W' 2

dV

V

= RT 2 ln ( V 4 )

V 3

This path is a reversible adiabatic path, Hence:

T 1

T

2

= ( V 4 )

V 1

( ϒ 1 )

→ Notice that

= ( V 4 V 1

= V 3

V 2

T

1

T

2

V 4

V 1

) ( ϒ 1 ) ; T 2

T 1

=( V 2 ) V 3

( ϒ 1 )

→ Efficiency (ε)

ε = 1 + q 2 = 1 +

q

1

T 2 ln ( V 4 )

V 3

T 1 ln ( V 2 )

V

1

= 1 T 2

T 1

→dS;

q

2

q

1

=− T 2 q 1 =− q 2

T 2

T

1

T 1

q

1

q 2 = 0 đq rev = 0

T

+

T 2 T 1

→Refrigerator Coefficient of Performance (η);

q
q 2
2
η =
−W = −( q 1
+ q 2 ) = heat extracted
Work entered
q
2
− T 2
q
T 1
T 2
1
=
=
−( q 1 + q 2 ) =
T 1 − T 2
−( 1 − T 2
)
T 1

η

→Generalize Carnot Engine Results:

T 1 ( hot )

q' 1

W

q 1 Another Rev . Engine

Carnot Engine

W'
 q 2 q' 2 T 2 ( hot )

ε =− W ;ε' = − W'

q' 1

q 1

Assume ε' > ε (totally wrong, but why?)

Use Work out of RH side to run LH backward. →Total Work out=0;

W' = W >0

ε' >ε q' W' 1

>

W

W > W

q' 1

q 1

W q 1 <q' 1 ;q 1 0 ( pumping heat up ) ; q ' 1 0 ( working as an engine )

q 1

q

1

=

That says

−( q' 1 + q 1 ) >0

And this is impossible!!!! So it says that the efficiency of any reversible engine must be:

ε =1 T 2 T 1

Entropy S is a state function:

dS=0 ;

And What about an Irreversible engine?

1→2

W irrev <W rev ;W irrev >W rev ; ΔU =q irrev +W irrev =q rev +W rev

Notice that ΔU is the same for both reversible and irreversible cases, Hence:

Efficiency (ε):

Clausius:

ε

q irrev <q rev

rev

irrev

rev = 1 + q q 1

irrev ;ε irrev = 1 + q irrev

2

2

q 1

ε rev >ε irrev

Thus, đq irrev

T

< đq rev

T

đq irrev

T

<0

đq irrev

T

0